Universal Work Function of Metal Oxides Exposed to Air. Issue 12 (6th May 2019) - Rietwyk, Kevin J.; Keller, David A.; Ginsburg, Adam; Barad, Hannah‐Noa; Priel, Maayan; Majhi, Koushik; Yan, Zhi; Tirosh, Shay; Anderson, Assaf Y.; Ley, Lothar; Zaban, Arie
Abstract: Metal oxides are the cornerstone of thin‐film electronics, a multibillion dollar industry, because they possess a wide variety of optoelectronic properties, exhibit novel functionalities, and can typically be fabricated from cheap, nontoxic raw materials. However, for thin‐film electronics to achieve further market penetration, it is necessary to replace expensive vacuum‐based fabrication processes with low‐cost, large‐scale solution‐based methods. Here, the influence of exposure to air on the band energies of metal oxides is investigated, which is crucial for predicting the operation of thin‐film devices under realistic conditions. A universal reduction in the work function is observed across 18 oxides, and for a subset, n‐type doping of the surfaces is observed after they have been exposed to atmosphere for extended periods of time. These effects arise from charge transfer events with the ubiquitous water layer that forms on surfaces in air. A quantitative analysis of the changes is provided based on the electrochemical transfer doping model, and the amount of transferred charge and the equilibrium work function of oxides in air are calculated which are in agreement with the measurements. Abstract : The ubiquitous water layer that forms on surfaces in air is shown to reduce the work function of 18 metal oxides via electrochemical transfer doping. For a subset of five oxides studied, this process is shown to n‐type dope the surface. Detailed modeling reveals that this doping promotes the work function to tend toward 4.7 eV.